EVALUATION OF EDUCATION MEASURING THE SUCCESS OF THE TEACHING AND LEARNING PROCESS IN A HOLISTIC WAY - Ahmad Taufiqur Rohman; Fitriyatul Hanifiyah; Moch. Sahroni (Program Studi Pendidikan Agama Islam, 2026)
This study was motivated by the dominance of educational evaluation that focused only on cognitive aspects, which was not able to measure learning success comprehensively. The purpose of this study was to analyze the concept of educational evaluation in measuring the success of the teaching and learning process holistically. This study used a library research method by reviewing relevant literature, which was analyzed using descriptive qualitative techniques through data collection, classification, content analysis, and synthesis. The results showed that holistic evaluation covered cognitive, affective, and psychomotor aspects and provided a more comprehensive description of student development. In addition, authentic assessment played an important role in its implementation. However, several challenges were still found in its application. Therefore, holistic evaluation was considered more effective in improving the quality of learning. Keywords: Educational Evaluation; Holistic Evaluation; Authentic Assessment; Learning Outcomes